当代海南的马来西亚和新加坡琼籍华人 文化资源之研究 - 叶, 晓静 (2022)
海南作为中国第三大侨乡，自1988年建省至2018年建设自由贸易港期间，充分利用马新琼籍华人文化资源，社会面貌发生巨大变化。什么是马新琼籍华人文化资源？这是本文的逻辑起点。通过梳理马新琼籍华人产生的历史脉络，发现马新琼籍华人与海南侨乡一直保持着密切联系。海南侨乡是如何广泛利用马新琼籍华人文化资源的？在挖掘会馆资料、侨眷家信、侨报侨刊等历史文献后，通过深入万宁、琼海两地进行田野调查，实地采访了29位相关人物口述历史，还原这三十年来海南利用马新琼籍华人文化资源最真实的情况。同时运用计量史学法进行数据整理分析，可见在教育文化资源、商业文化资源、公益文化资源三个方面影响面最广。大量第一手资料的呈现，以及拓宽了目前海南华人研究的时间和空间范围，这是本文研究的意义所在。 而马新琼籍华人倾注巨大的热情，其行为背后内含根祖文化、人文精神以及现代价值，这是华人与侨乡在情感或者现实两方面都需要的。 近年来马新琼籍华人与海南侨乡互动不再频繁，不可避免地所呈现的社会关系日渐衰落。通过研究发现，马新侨情新变化、马新侨企出现的深层次问题、对马新琼籍华人文化资源利用意识的淡薄、观念差异及信息不对称、政策不确定性及不连续性问题，都是导致这一现象产生的根本的原因。本文亦重新思考双方角色定位、互动交流的形式，提倡培育既有民族特色又适应时代潮流的互惠原则，重构现代马新琼籍华人与祖籍地的情感联结，从而充分发展和利用马新琼籍华人文化资源。 As the third largest hometown of overseas Chinese in China, Hainan has made substantial of the cultural resources of Malaysia and Singapore Hainanese from the establishment of the province in 1988 to the construction of the free trade port in 2018, and the social landscape has undergone tremendous changes. What is the cultural resources of Malaysia and Singapore Hainanese? This is the logical starting point of this article. By sorting out the historical context of the origin of the Malaysia and Singapore Hainanese, it is found that the Malaysia and Singapore Hainanese have always maintained close ties with the hometown of overseas Chinese in Hainan. How did the overseas Chinese hometown of Hainan make extensive use of the cultural resources of Malaysia and Singapore Hainanese? After excavating historical documents such as guild hall materials, family letters from overseas Chinese, overseas Chinese newspapers and magazines, etc., through in-depth field investigations in Wanning and Qionghai, through interviewing and collecting 29 related people's oral histories, the researcher able to restored the actual use of the cultural resources of Malaysia and Singapore Hainanese in Hainan in the past 30 years. At the same time, the study also adopts the method of quantitative history to organize and analyze the data, it can be seen that the three aspects of educational cultural resources, commercial cultural resources, and public welfare cultural resources have the most extensive influence. The presentation of a large number of first-hand materials and the broadening of the time and space scope of the current Hainan Chinese research are the significance of this study. With great enthusiasm, the contribution of Malaysia and Singapore Hainanese to Hainan society comprises the elements of ancestral culture, humanistic spirit and modern values, either emotionally or realistically. In recent years, the interaction between Malaysia and Singapore Hainanese and the overseas Chinese hometown in Hainan has become less frequent, and the social relationship has gradually declined. Through the research, it is found that the reasons for this phenomenon are due to the new changes in the situation of Malaysia and Singapore Hainanese, the deep-seated problems of overseas Chinese enterprises in Malaysia and Singapore, the lack of awareness of the use of cultural resources of Malaysia and Singapore Hainanese by the overseas Chinese hometown in Hainan, the difference in concepts and information asymmetry, the uncertainty and discontinuity of policies. This paper also rethinks the roles of the two sides and the form of interaction and communication in between, cultivates the principle of reciprocity that has both national characteristics and adapts to the trend of the times, reconstructs the emotional connection between the modern Malaysia and Singapore Hainanese and the ancestral place, so as to develop and utilize the Cultural resources of Malaysia and Singapore Hainanese in the future.